Development of Klebsiella pneumoniae Capsule Polysaccharide-Conjugated Vaccine Candidates Using Phage Depolymerases - Lin, Tzu-Lung; Yang, Feng-Ling; Ren, Chien-Tai; Pan, Yi-Jiun; Liao, Kuo-Shiang; Tu, I-Fan; Chang, Yu-Pei; Cheng, Yang-Yu; Wu, Chung-Yi; Wu, Shih-Hsiung; Wang, Jin-Town (Frontiers in Immunology, 2022)
Klebsiella pneumoniae is an important pathogen associated with nosocomial infection and has developed increasing resistance to antibiotics such as extended-spectrum b-lactams and carbapenem. In recent years, K. pneumoniae isolates have emerged as a major cause of global community-acquired infections such as pneumonia and pyogenic liver abscess. Although serotypes K1 and K2 have been identified as the predominant capsular types associated with invasive infections, no K. pneumoniae vaccine is commercially available, probably due to immunogenicity loss in the traditional depolymerization method to obtain capsule polysaccharide (CPS) for the preparation of conjugated vaccine. In this study, we successfully retained immunogenicity by using K1 (K1-ORF34) and K2 (K2-ORF16) CPS depolymerases that were identified from phages to cleave K1 and K2 CPSs into intact structural units of oligosaccharides with intact modifications. The obtained K1 and K2 oligosaccharides were separately conjugated with CRM197 carrier protein to generate CPS-conjugated vaccines. Immunization experiments of mice showed both K1 and K2 CPS-conjugated vaccines induced anti-CPS antibodies with 128- fold and 64-fold increases of bactericidal activities, respectively, compare to mice without vaccinations. Challenge tests indicated that K1 or K2 CPS-conjugated vaccine and divalent vaccine (a mixture of K1 and K2 CPS-conjugated vaccines) protected mice from subsequent infection of K. pneumoniae by the respective capsular type. Thus, we demonstrated K1 and K2 CPS-conjugated vaccines prepared by CPS depolymerases is a promising candidate for developing vaccines against human K. pneumoniae infections.